Swiss Franc from the Croatian Perspective - Mile Bošnjak (Journal of Central Banking Theory and Practice, 2018)
In Croatia and other countries of Central and Eastern Europe, as a consequence of deep financial integration and abolition of capital controls, considerable loans to households indexed to the Swiss franc have emerged. Although all of researchers of the Swiss franc do not agree entirely on whether the Swiss franc is a safe haven currency, its property of continuous appreciation is commonly accepted. There was a continuous appreciation of the Swiss franc over the Croatian kuna. This paper examines the performance of several ARCH-based models for Swiss franc against the Croatian kuna on daily data sets within time period from 1997 to 2010. Evaluating the models through standard information criteria Component ARCH (1,1) is found to be the best-fitting model.
Keywords: C13; C58; F31; F32; G15; 330; Swiss franc; asymmetric GARCH; exchange rate; Croatia